6-Benzylaminopurine and 3-Indolebutyric acid on the in vitro multiplication of Eugenia involucrata - Moro Stefanel, Charlene; Silveira Reiniger, Lia Rejane; Lemos Serrote, Caetano Miguel (Revista Ceres, 2025)
Eugenia involucrata is an important Brazilian forest species, which it can be used for timber, such as firewood and charcoal, and non-timber purposes, for culinary and medicinal use. Considering the limitations of its seminal reproduction, vegetative propagation, particularly by micropropagation, becomes an alternative for plantlets production. In this study we evaluated the effect of the phytoregulators 6-benzylaminopurine (BAP) and 3-indolebutyric acid (IBA) on the in vitro multiplication stage of nodal segments. The experiment was carried out in a completely randomized design, in a 3 x 4 factorial array, the main factors were BAP (0; 0.1 or 0.2 µM) and IBA (0; 10; 20 or 30 µM). After 60 days of in vitro inoculation, evaluations on the the number of buds, number of shoots, number of leaves, callus formation (%) and number of roots per explant were carried out. BAPhad not significant effect, however, the use of IBA alone favours the callogenesis and negatively affected leaves, shoots and roots formation. A moderate multiplication rate was obtained when considering in vitro bud formation. BAP and IBA are dispensable in in vitro multiplication of E. involucrata.